PERAN MAHASISWA DALAM GERAKAN ANTI KORUPSI - Muhammad Amar Ma’ruf; Guruh Aryo Santoso; Afifah Mahdiy Mufidah (UNES Law Review, 2019)
Corruption is a problem and is a big challenge faced by the people of Indonesia and the world. Corruption has been around for a long time since humans have known administrative governance. Corruption is often related to problems or political policies in the government environment. Corruption is included as criminal behavior, corruption is not just stealing, but there is an element of abuse of authority or power in it, it gives moral content to corruption. Corruption does not only affect one aspect of life but also has a domino effect on other aspects of life. One of the best ways to break the chain of corruption in this country is by providing anti-corruption education to the next generation of its people. Because the next generation of the nation will be the generation that replaces the old state officials, to build a beloved country so that it can triumph in the eyes of the world. This young generation is the key to the success of the country's development which must avoid corruption. So, it is easier for us to educate and influence the younger generation so that they do not commit criminal acts of corruption before they are first influenced by the "culture" of corruption from their predecessor generation. Students are supported by the basic competencies they have, namely: intelligence, creative ideas, critical thinking skills, and the courage to express the truth. With their competence, students are expected to be able to become agents of change for themselves, their families, and the surrounding community, they are able to voice people's interests, are able to criticize corrupt policies, and are able to become supervisors of state institutions and law enforcement.